High-performance gel filtration patterns of venoms from three species of wasps of the genus Polybia (hymenoptera, vespidae). - Palma, Mario Sergio [UNESP] (1996)
The profiles of high-performance gel filtration of venoms from Polybia paulista, Polybia ignobilis and Polybia occidentalis occidentalis showed 13 peaks distributed among the three species. These profiles presented similarities that permitted the chromatographic characterization of the genus Polybia and differences that permitted the identification of each species studied. Thus, the comparative analysis of chromatographic profiles of high-performance gel filtration of venoms may be used as an auxiliary tool in taxonomic studies of Polybia wasps.